PENGARUH TINGKAT SUKU BUNGA, JANGKA WAKTU DAN PENYALURAN KREDIT TERHADAP KREDIT MACET PADA PT.BANK TABUNGAN PENSIUNAN NASIONAL KCP ENDE - Isa, Hafifah Sufina; Ismail, Nuraini; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2022)
The purpose of this study to determine the effect of interest rates, term and lending to bad loans at PT. National Pension Savings Bank KCP.Ende. Collecting data using a questionnaire survey and the sample is customers who make loans to PT. BTPN. The data collected was processed using the SPSS program. The results of the study show that: (1) Interest Rates have an effect on Bad Loans, this is evidenced by the coefficient value of the interest rate variable of 0.221 with tcount > ttable (2.208 > 1.98667) and a significant level of 0.030 <0.05. (2) Term has an effect on Bad Loans, this is evidenced by the coefficient value of the Term variable of 0.222 with tcount > ttable (2.423 > 1.98667) and a significant level of 0.017 <0.05. (3) Credit Distribution has an effect on Bad Loans, this is evidenced by the coefficient value of the Credit Distribution variable of 0.133 with tcount > ttable (2.139 > 1.98667) and a significant level of 0.035 < 0.05.